Facts About Magnesium - Linda B. Bobroff; Jennifer Hillan (EDIS)
Many Americans don’t get enough magnesium in their diets. But most healthy people do not have signs of deficiency even if their intake is low because the body stores this mineral. However, people who abuse alcohol, take certain diuretic drugs, or have kidney disease may be at risk for magnesium deficiency. Long-lasting diarrhea or vomiting also can cause a deficiency. Older adults often do not get enough magnesium in their diets. This 2-page fact sheet was written by Linda B. Bobroff and Jennifer Hillan and published by the UF Department of Family Youth and Community Sciences, July 2013.